2018
DOI: 10.7326/m17-3088
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting Hepatitis C Virus–Infected Versus Uninfected Kidneys Into Hepatitis C Virus–Infected Recipients

Abstract: Merck Sharp & Dohme and the National Center for Advancing Translational Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Gupta and colleagues analyzed the cost of effectiveness of transplanting a HCV‐positive organ and post‐transplant DAA therapy and found that such a strategy resulted in an increased year of life with an expected cost of $100k US dollars less compared to continuing hemodialysis and waiting for a HCV‐negative donor . Eckman's sensitivity analysis suggested that transplant of an HCV‐uninfected donor kidney preceded HCV treatment was preferred only if the additional wait time for an uninfected donor kidney was less than 161 days . Given this cost‐effectiveness and the low risk of transmission from our center's experience, the utilization of aviremic HCV kidneys appears to be an effective strategy to expand the donor pool and to increase transplant volume.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta and colleagues analyzed the cost of effectiveness of transplanting a HCV‐positive organ and post‐transplant DAA therapy and found that such a strategy resulted in an increased year of life with an expected cost of $100k US dollars less compared to continuing hemodialysis and waiting for a HCV‐negative donor . Eckman's sensitivity analysis suggested that transplant of an HCV‐uninfected donor kidney preceded HCV treatment was preferred only if the additional wait time for an uninfected donor kidney was less than 161 days . Given this cost‐effectiveness and the low risk of transmission from our center's experience, the utilization of aviremic HCV kidneys appears to be an effective strategy to expand the donor pool and to increase transplant volume.…”
Section: Discussionmentioning
confidence: 99%
“…No patients had treatment‐related adverse events and none had detectable HCV RNA 12 weeks after treatment . Lastly, a more recent modelling analysis suggests this strategy has the additional benefit of being cost‐effective because transplanting HCV‐infected donor kidneys into HCV‐infected recipients decreases patients’ time on the waitlist and therefore also their time on haemodialysis . While these preliminary data are promising, without large prospective studies, we cannot yet draw conclusions about adopting this strategy on a larger scale.…”
Section: Renal Transplantation With Hcv‐positive Organsmentioning
confidence: 95%
“…An increasing experience has attested to a lack of adverse consequences for graft or recipient when these organs are implanted into already HCV-infected patients. 10 12 In the United States, the consensus is increasingly that HCV therapy is best deferred in HD patients who are transplant candidates to allow receipt of a kidney from an HCVpositive donor. 13 Such a policy is feasible due to the efficacy and tolerability of DAA after renal transplantation.…”
Section: Consequences Of Hcv Infection For An Individual Patient Not mentioning
confidence: 99%
“…Acceptance of an organ from an HCV‐positive donor under the current organ allocation system in the United States can substantially reduce individual waiting times. A recent Markov model endorsed a strategy of acceptance of kidney grafts from HCV‐positive donors for HCV‐infected recipients deferring antiviral therapy until after transplant . In the United States, the consensus is increasingly that HCV therapy is best deferred in HD patients who are transplant candidates to allow receipt of a kidney from an HCV‐positive donor .…”
mentioning
confidence: 99%